PT.GARUDA INDONESIA AIRWAYS (TBK) REVIVAL: A STRATEGIC DEBT RESTRUCTURING AND BUSINESS TRANSFORMATION AGAINST BANKRUPTCY - Sazly, Syukron; Erri, Dirgahayu; Prana, Indra; Dewi, Intan Kusuma (Universitas Muhammadiyah Tangerang, 2024)
This study aims to examine the financial challenges faced by PT Garuda Indonesia (Tbk) between 2021 and 2023, focusing on its efforts in debt restructuring and business transformation, as well as the impact of these initiatives on its financial recovery. Using a descriptive research approach, the study analyzes quantitative data, including the Springate S-Score model, which assesses bankruptcy risk by evaluating key financial ratios. The findings show that Garuda experienced severe financial distress in 2021, reflected in a significantly low Springate S-Score, indicating a high likelihood of bankruptcy. Although there was a brief recovery in 2022, the score dropped again in 2023, signaling continued financial risks primarily due to high debt levels and operational inefficiencies. The research identifies that the airline's issues stemmed from excessive leasing costs, poor financial oversight, and the impact of the COVID-19 pandemic on air travel. While debt restructuring and business transformation efforts, including streamlining operations and expanding revenue sources, showed positive outcomes, the Springate S-Score still highlights the company's vulnerability. The Springate S-Score and relevant financial ratios for PT Garuda Indonesia from 2019 to 2024, with all years classified under